Regio-selective PEGylation of 14-deoxy-11, 12-didehydroandrographolide and their biological evaluation. Issue 39 (29th September 2016) - Wang, Zhen; He, Ru; Chen, Yi; Wu, Feipeng
Abstract: Poor water solubility limits the clinical use of 14-deoxy-11, 12-didehydroandrographolide (DA ). To develop a simple and efficient approach to improving water solubility ofDA, polyethylene glycol methyl ether (mPEG350, average MW=350) as hydrophilic group is employed. Two PEGylatedDA derivativesDA-1 (mPEG350 at C19 -position) andDA-2 (mPEG350 at C3 -position) are synthesized and evaluated to inhibit the cell proliferation of HepG-2 cells in vitro. As expected, the aqueous solubility ofDA-1 andDA-2 is significantly improved (ca. 200 mg/mL, 25 °C), and both exhibit good partition coefficient (log P≥1.6). It is found thatDA-1 shows tumor-inhibition activity and more than 60% cell inhibition is obtained. Graphical abstract: